Efecto de la risperidona en el comportamiento psicótico inducido por ketamina y su relación con los niveles de malondialdehido en cerebro de rattus norvegicus var. albinus - Díaz Gamarra, Yesennia Giovana (2014)
This research was based on determining the effect of risperidone in psychotic behavior induced by ketamine and its relationship with Malondialdehyde levels in brains of Rattus norvegicus var. albinus. Randomly distributed into four groups of six specimens each (White, Control Problem Problem I and II) was performed. At the White group was given intraperitoneally Physiological Saline at a dose of 10 mL / kg for 10 days and then orally for 31 days; The control group was administered intraperitoneal ketamine at a dose of 20mg / kg for 20 days and subsequently orally water ad libitum for 11 days at 20mg / kg. At Problem Problem I and II groups were administered intraperitoneal ketamine at a dose of 20mg / kg for 20 days, but on the tenth day of treatment was administered orally to parallel Risperidone 1mg / kg and 2.5mg / kg, respectively . After this process, the psychotic behavior to all groups of specimens were evaluated using models Open Field and Rota Rod. The variables analyzed in the Open Field were square advanced, bipedal, invasion holes, defecation and self-cleaning, and the Rota Rod was the time spent on the rotating rod. The result obtained with the Open Field model was an increase in locomotion in the control group compared to the other groups, primarily the problem compared to group II. More statistically significant difference (p <0.05) was evident in the variables of squares advanced and intrusion into holes. With respect to Rota Rod statistically significant difference (p <0.05) between the control group and blank group, the result was that ketamine lengthens the residence time of the specimens was observed in the team; however, risperidone groups tend to resemble the target group. Later levels of oxidative stress, which show a statistically significant difference (p <0.05) between control and target groups showing high levels of MDA for the first, were evaluated also showed that there are significant differences (p <0.05) between the control group and groups I and II problem, expressing low levels of MDA for the last groups. In conclusion, this study demonstrates that reverses Risperidone psychotic effect induced with ketamine, in which the dose where the effect is best seen 2.5mg / kg; further has a protective antioxidant effect-in the same above dose, by decreasing levels of oxidative stress, expressed by MDA concentrations in brain, and can be regarded as an added value to the clinical effects of the atypical antipsychotic